2022
DOI: 10.1007/s00420-022-01845-9
|View full text |Cite
|
Sign up to set email alerts
|

Sleep of recruits throughout basic military training and its relationships with stress, recovery, and fatigue

Abstract: Objective Studies in basic military training (BMT) examining sleep are largely cross-sectional, and do not investigate relationships between sleep, stress, recovery and fatigue. The aims of this study were to (1a) quantify changes in recruits’ sleep quantity and quality over 12 weeks of BMT; (1b) quantify changes in recruits’ perceptions of stress, fatigue and recovery over BMT; and (2) explore relationships between sleep, and perceptions of stress, fatigue and recovery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
2
6
0
1
Order By: Relevance
“…For example, that more experienced officers were more likely to frequently provide recovery periods when fatigue was identified may have been related to a greater understanding of the ability or need to prioritize rest in different situations based on operational needs. Furthermore, consistent with previous studies of military service members, worse sleep quality predicted more fatigue [ 6 , 10 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For example, that more experienced officers were more likely to frequently provide recovery periods when fatigue was identified may have been related to a greater understanding of the ability or need to prioritize rest in different situations based on operational needs. Furthermore, consistent with previous studies of military service members, worse sleep quality predicted more fatigue [ 6 , 10 ].…”
Section: Discussionsupporting
confidence: 90%
“…Such factors can disrupt sleep and alertness if individuals’ daily schedules become misaligned with the timing signals generated by their internal circadian rhythms [ 7 , 8 ]. As a case in point, short sleep has consistently been observed aboard US Navy (USN) warships, whether measured using self-report surveys (mean ± standard deviation; 5.26 ± 1.23 hours) [ 6 ] or actigraphy (6.60 ± 1.01 hours) [ 9 ] and fatigue has been associated with several deadly and costly at-sea mishaps [ 10–13 ]. These prominent threats to safety, among other consequences of fatigue, underscore the need for an effective fatigue management system (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This study was approved by the Department of Defence and Veteran’s Affairs Human Research Ethics Committee (021-17). An overview of activities completed during BMT has been previously described [ 32 , 33 ], while sleep duration for these recruits has also been reported [ 33 ]. Activities included training related to military skills and equipment, marksmanship, and combat manoeuvres, and culminated in a 10-day field training phase which involved sleep restriction, physical and cognitive demands, and outdoor sleeping and night activities (e.g., picket).…”
Section: Methodsmentioning
confidence: 99%
“…Although it has been known since time immemorial that different emotions can be experienced during initial active duty for training [6], it can be argued that these emotions can also affect other health factors such as mental and physical health and sleep quality. In a study, it was found that there were strong relationships between subjective sleep quality and stress, rest, and fatigue in initial active duty for training for 12 weeks [7]. In addition, soldiers, firefighters, correctional officers, and paramedics experience more mental health problems as they are exposed to more psychological traumatic events in their lives than other individuals [8].…”
Section: Introductionmentioning
confidence: 99%